Closing the Leadership Gap in Asia - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Emerging Asian markets – which are expected by the International Monetary Fund to grow by 8.5 percent in 2014 – are indispensable for any large firm with aggressive growth commitments. Although such projections may prove optimistic, companies still rely on Asia to compensate for under-performing mature markets. CEOs in Asia report that their targets for regional business units average 5 percent above the rate of regional economic growth — a target that can only be reached by capturing significant market share from the competition. Over-performing in hypercompetitive Asian markets depends, in large part, on the quantity and quality of Asia leadership teams. Unfortunately, qualified leaders are in short supply in the region. Recognising that leadership is the essential ingredient for success, senior executives ranked Leadership Performance and Retention as one of Asia‘s top-three business risks in CEB‘s survey of CEOs in Asia.